2004
DOI: 10.2337/diacare.27.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidant Intake and Risk of Type 2 Diabetes

Abstract: OBJECTIVE -The intake of antioxidants was studied for its ability to predict type 2 diabetes.RESEARCH DESIGN AND METHODS -A cohort of 2,285 men and 2,019 women 40 -69 years of age and free of diabetes at baseline (1967)(1968)(1969)(1970)(1971)(1972) was studied. Food consumption during the previous year was estimated using a dietary history interview. The intake of vitamin C, four tocopherols, four tocotrienols, and six carotenoids was calculated. During a 23-year follow-up, a total of 164 male and 219 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
255
9
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(283 citation statements)
references
References 34 publications
14
255
9
5
Order By: Relevance
“…This relation is still controversial, as studies examining dietary and serum antioxidants with type 2 diabetes show inconsistent results ranging from no relation to an inverse relation for certain antioxidants [41,42]. A recent randomised crossover trial, however, showed that chlorogenic acid and trigonelline significantly lower glucose and insulin [37].…”
Section: Discussionmentioning
confidence: 99%
“…This relation is still controversial, as studies examining dietary and serum antioxidants with type 2 diabetes show inconsistent results ranging from no relation to an inverse relation for certain antioxidants [41,42]. A recent randomised crossover trial, however, showed that chlorogenic acid and trigonelline significantly lower glucose and insulin [37].…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids, vitamin C, and vitamin E may have a protective effect against development of diabetes by relieving oxidative stress that interferes with the glucose uptake by cells (Halliwell & Gutteridge, 1989;Gordon, 1996). In several epidemiological studies, intakes or serum levels of vitamin C, vitamin E, or carotenoids have been inversely associated with diabetes (Chatterjee & Banerjee, 1979;Sinclair et al, 1994;Feskens et al, 1995;Salonen et al, 1995;Abahusain et al, 1999;Ford et al, 1999;Knekt et al, 1999;Will et al, 1999;Polidori et al, 2000;Montonen et al, 2004b). However, the findings on the relation between antioxidants and glucose metabolism are not consistent (Sanchez-Lugo et al, 1997;Reunanen et al, 1998;Liu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A long drawn study of 23 yr follow up in a cohort in Finland consisting of 2285 men and 2019 women for 4 tocopherols, 4 tocotrienols, 6 carotenoids and ascorbic acid showed that dietary intake of these of antioxidants reduced the risk of DMT-2 (126). The flaw of this study is that it took only these antioxidants from the diet into consideration whereas the diet contains a large number of other ingredients which might be exerting beneficial effects, such as variability of the diet appears to be a telling confounding factor in this study.…”
Section: Antioxidant Therapy and Supplementsmentioning
confidence: 99%